Quantifying offense and defense workloads in professional Rugby Union - Stevens, L. J.; Hopkins, W. G.; Chittenden, J. A.; Koper, B. Z.; Smith, T. B. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Rugby union is a contact team sport demanding high levels of physical capacity, and understanding the match workloads can be useful to inform training. In this study, the factors influencing locomotion and contact workloads for offensive and defensive ball-in-play periods are quantified.